2019
DOI: 10.1021/acs.jpcc.9b06850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Charge-Assisted Hydrogen Bonds on Single-Molecule Electron Transport

Abstract: The effect of the in-backbone presence of charge-assisted hydrogen bonds (CAHBs) in the conductance of single-molecule junctions has been studied by the scanning tunneling microscope break junction technique. In particular, two amidinium−carboxylate supramolecular complexes of different lengths have been tested. We observed that the ionic character that gives extra stability to the CAHB is a hindrance toward the electron transport through the complexes. Theoretical calculations using the DFT + Σ method indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“… Schematics of typical H‐bonded junctions from DNA base pairs to Upy dimer (a–d) [10, 63] . Schematic of CAHBs junction (e) and the 1D conductance histograms of monomer (f, blue) and dimer (f, purple) [34b] . (g) Localized electron distribution of CAHBs dimer.…”
Section: Supramolecular Junctions With Non‐covalent Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“… Schematics of typical H‐bonded junctions from DNA base pairs to Upy dimer (a–d) [10, 63] . Schematic of CAHBs junction (e) and the 1D conductance histograms of monomer (f, blue) and dimer (f, purple) [34b] . (g) Localized electron distribution of CAHBs dimer.…”
Section: Supramolecular Junctions With Non‐covalent Interactionsmentioning
confidence: 99%
“…studied the effect of charge‐assisted hydrogen bonds (CAHBs) on H‐bonded junctions (Figure 14e). [34b] CAHBs means that ion‐charged H‐donor and H‐acceptor enhance the hydrogen bond strength. Experimental studies found that the formation probability of SMe‐anchored CAHBs junctions reaches up to 67 %.…”
Section: Supramolecular Junctions With Non‐covalent Interactionsmentioning
confidence: 99%
“…The histogram of compound 2 is also shown for comparison. Reproduced with permission, [ 68 ] Copyright 2019, American Chemical Society.…”
Section: Hydrogen‐bonded Molecular Junctionsmentioning
confidence: 99%
“…[ 14,20 ] The building units of CAHONs often possess the acid and base sites, in other words, the acidity and basicity of involved ligands are generally selected as oppositely charged building units for constructing stable CAHONs. [ 21‐23 ] It is well‐known that carboxylic acid can be deprotoned and becomes the anionic building block, while the viologen often possesses the positive charges, which is a good candidate for the cationic building unit. [ 24‐26 ] The combination of the electron‐rich carboxylic acid and the electron‐deficient viologen is an efficient method for probing the novel CAHONs with specific functional properties.…”
Section: Background and Originality Contentmentioning
confidence: 99%